2018
DOI: 10.3390/ijms19082327
|View full text |Cite
|
Sign up to set email alerts
|

Developing Hollow-Channel Gold Nanoflowers as Trimodal Intracellular Nanoprobes

Abstract: Gold nanoparticles-enabled intracellular surface-enhanced Raman spectroscopy (SERS) provides a sensitive and promising technique for single cell analysis. Compared with spherical gold nanoparticles, gold nanoflowers, i.e., flower-shaped gold nanostructures, can produce a stronger SERS signal. Current exploration of gold nanoflowers for intracellular SERS has been considerably limited by the difficulties in preparation, as well as background signal and cytotoxicity arising from the surfactant capping layer. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The shift in the plasmonic band was expected because of the differences in the dielectric environment, as highlighted by Evans et al in a SERS study. 31 It is important to emphasize that Au-based NIR nanoparticles that respond to light in the NIR range of 650−950 nm can prevent damage to surrounding healthy tissues as well as enable sufficient light depth of penetration in tissues to provide sufficient photothermal efficiency. 32 In this context, healthy cells are resistant to photothermal therapy, as observed in Figure 7b.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The shift in the plasmonic band was expected because of the differences in the dielectric environment, as highlighted by Evans et al in a SERS study. 31 It is important to emphasize that Au-based NIR nanoparticles that respond to light in the NIR range of 650−950 nm can prevent damage to surrounding healthy tissues as well as enable sufficient light depth of penetration in tissues to provide sufficient photothermal efficiency. 32 In this context, healthy cells are resistant to photothermal therapy, as observed in Figure 7b.…”
Section: Resultsmentioning
confidence: 68%
“…Although this intracellular plasmonic effect probably did not alter the PTT property of our AuNF because of their broad NIR band, as observed in PTT results. The shift in the plasmonic band was expected because of the differences in the dielectric environment, as highlighted by Evans et al in a SERS study …”
Section: Results and Discussionmentioning
confidence: 80%
“…By changing the core size, number, length, and width of the sharp branches, the absorption band of branched gold nanostructures can be adjusted to the NIR region. In addition, branched gold nanostructures have a large surface area, and the “hot spots” at their sharp corners greatly enhance the intensity of the surrounding electromagnetic field, endowing them with a large surface enhanced Raman scattering (SERS) effect and broad application prospects [ 75 , 76 , 77 ].…”
Section: Noble Metal Nanomaterialsmentioning
confidence: 99%
“…On this basis, Pissuwan and Hattori ( 14 ) designed a surface-enhanced Raman scattering gold nanorod probe specifically for binding endothelial intercellular adhesion molecule-1 produced by macrophages and the part of cytokines that stimulates endothelial cells in order to enhance Raman signals and achieve better imaging results at the cellular level ( Figure 2 ). A facile method of fabricating hollow-channel gold nanoflowers without surface activators for surface-enhanced Raman scattering was recently developed by the Ye et al ( 15 ), and the trimodal nanoprobes demonstrated effective cellular internalization and low cell toxicity. The development of less toxic silver or gold nanoparticles with highly specific particles will be possible in the near future for use in vivo with emission profiles to allow in-depth analysis of tissues.…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 99%